RISK MANAGEMENT ANALYSIS OF CASH WAQF: CASE STUDY OF BMT WAKAF YAYASAN INVESTA CENDEKIA AMANAH JAKARTA - Alamsyah Muslaen Pawelangi; Rahma Yudi Astuti (Islamic Business and Management Journal, 2018)
Currently waqf is not just immobile objects that are musholla, mosque, school, orphanage, and grave. However, there are also waqf managed productively such as money waqf. the institution that manages the cash waqf is called nazhir. Institutions that wish to manage the cash waqf must obtain permission from the Indonesian Waqf Board (BHI). Therefore, BMT Wakaf Yayasan Investa Cendekia Amanah is trusted by BWI to manage cash waqf. So in its management, BMT must manage risk well. Risk has become a common thing caused by the existence of uncertainty and has been regarded as sunnatullah life. The purpose of this study is to determine and analyze the risks of what is contained in Islamic micro finance institutions such as BMT. In addition, to find out how to manage the risk of cash waqf during which it is used to invest the principal of the waqf funds. The method used in this study is a qualitative method using three different techniques of interview, documentation, and participatory observation. sources of information taken in this study include the Chairman of Board and treasurer in the form of interviews, documentation data, and observation results in the field. Findings in the field indicate that BMT Wakaf Yayasan Investa Cendekia Amanah has not fully manage the risk of cash waqf funds well so that the financing has stalled. especially in murabahah and ijarah financing, which is followed by the use of large funds of cash waqf, causing loss and loss of the cash waqf substance. Therefore, BMT Wakaf Yayasan Investa Cendekia Amanah must improve the ideal management capacity in managing risk including prudential principles in providing financing to customers, and need cooperation with insurance institutions to cover cash waqf loss.Keywords: Cash waqf, nazhir, Risk management.